Carta de Jorge Cestero Mangual a Roberto H. Todd - Cestero Mangual, Jorge; Todd, Roberto H. (My University, 1942)
Artículo sobre el General Townshed.
Keywords: Puerto Rico. Department of the Interior; Puerto Rico--Política y gobierno.; Puerto Rico--Politics and government.; Townshed, Arnald P.